KOMPOSISI HASIL TANGKAPAN DAN DISTRIBUSI UKURAN CUMI-CUMI (Loligo chinensis, Gray 1849) DENGAN MENGGUNAKAN ATRAKTOR DI PERAIRAN SELAT MAKASSAR - Dananjaya, Wayan Kantun; Merliana, Merliana Merliana; Kabangga, Arnold Kabangga (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2023)
Squid is one of the marine fishery commodities that is widely used by the public, causing increasing demand. This research aims to determine the composition and size distribution of squid catches based on attractor color. The research used three attractor colors, namely white, black and blue and operated in the waters of the Makassar Strait for 12 trips on a squid fishing boat using hand lines. The results of the research showed that the catch was 149 individuals with a composition of 16.11% caught on white attractors, 32.21% caught on black attractors and 51.68% caught on blue attractors. Weight distribution of squid using white attractor ranges from 10-55 g (29.75 ± 12.86 g), tentacle length 6-15.3 cm (8.94 ± 2.35 cm), black attractor 15-99 g (36.58 ± 17.63 g) tentacle length 7.5-20 cm (10.33 ± 2.34 cm) and blue attractor 15-95 g (46.62 ± 21.93 g) tentacle length 7-19 .2 cm (11.39 ± 2.84 cm). The composition of the catch, the distribution of mantle length and the largest weight were obtained from the blue attractor.